An Investigation of the Effects of Holographic Wristbands on Strength, Balance and Flexibility - a Double-Blind Placebo Controlled Study - ÖZGÜL, BAHAR; TİMURTAŞ, EREN; POLAT, MİNE GÜLDEN; AYDOĞDU, ONUR; YURDALAN, SAADET UFUK; SARI, ZÜBEYİR (SOC PHYSICAL THERAPY SCIENCE, 2012)
[Purpose] This study investigated the effects of holographic wristbands on strength, balance and flexibility. [Subjects and Methods] The study included 43 healthy university students, 15 females (34.88%) and 28 males (65.12%), attending the Department of Physiotherapy and Rehabilitation at Marmara University. The age of the participants ranged from 19 to 27 (mean age 21.2 +/- 1.7 years). Strength, balance with eyes open, balance with eyes closed and flexibility were evaluated under four different conditions of wearing holographic EFX (R), PWX (R) and placebo wristbands, and no wristband. [Results] In evaluations of strength, balance with eyes are open, balance with eyes closed and flexibility, a significant difference was observed in favor of the placebo wristband compared to the PWX (R) wristband. For the other tests, holographic wristbands had no effect on strength, flexibility or balance with eyes closed. [Conclusion] It was concluded that holographic wristbands, which are marketed asergogenic aids, have no effect on strength, balance or flexibility.
Keywords: Holographic technology; Wristband; Balance; ERGOGENIC AIDS; PERFORMANCE; ADULTS; SPORTS